Analysis on frequency of missing mandibular first molar in medium aged adults – A Retrospective study - ANAND, SHREYA SVITLANA; V, ASHOK; RAMAMURTHY, JAIGANESH (The journal of contemporary issues in business and government, 2021)
The retrospective study was conducted among patients visiting the out patient department of a private hospital, Chennai. The aim of the study was to identify the frequency of missing mandibular first molars in medium aged adults. Patients belonging to age group 35 to 75 years with missing mandibular first molar and patients who underwent extraction of mandibular first molar from June 2019 to March 2020 were selected for the study . The patients undergoing replacement of the missing teeth were also evaluated. The data was entered into the SPSS software by IBM and analyzed by descriptive analysis and Pearson correlation. The study population consisted of 1099 patients with missing or extracted mandibular first molar within the age group 35 to 75 years. We observed that the frequency of missing mandibular first molar is 12% among the medium aged adult population with missing teeth. Maximum number of patients with missing mandibular first molar belonged to the age group 35 to 45 years (66.33%) [p value= 0.002 - significant]. Around 50.05% of the study population did not undergo any replacement procedure and 49.95% underwent prosthodontic treatment for replacement of the missing mandibular first molar teeth .Out of which 23% underwent implant , 20.1% underwent TPD, 7% underwent Fixed dental prosthesis . The remaining 47.4% of the population did not undergo treatment of missing / extracted teeth .